Dynamic Online Planning and Scheduling Using a Static Invariant-Based Evaluation Model - Pralet, Cédric; Verfaillie, Gérard (Proceedings of the International Conference on Automated Planning and Scheduling, 2013)
Sequential decision-making under uncertainty often uses an approach in which a plan is built over a given horizon ahead using a deterministic model, the first decisions in this plan are applied, new information is acquired, the plan is adapted or rebuilt from scratch over a sliding horizon, and so on. This paper introduces a generic local search library that can be used in this context to quickly build and rebuild good quality plans. This library is built upon the notion of invariant used in constraint-based local search. Invariants allow temporal constraints, resource constraints, and criteria to be very quickly evaluated from a variable assignment and re-evaluated from a small change in this assignment. The paper also shows how the library can be used to reason on dynamic problem instances using a unique static problem model, without dynamic memory allocation. The approach is illustrated on a problem of data download under uncertainty about the volume of data, coming from the space domain.